Attenuation of Enterococcus faecalis biofilm formation by Rhodethrin: A combinatorial study with an antibiotic. (February 2022) - Tatta, Eswar Rao; Kumavath, Ranjith
Abstract: The nosocomial pathogen Enterococcus faecalis critically implicated in the hospital environment. Its major virulence attributes biofilm formation and antibiotic resistance. The novel therapeutics are required to inhibit E. faecalis biofilm formation and virulence. Thus combinatorial and drug repurposing has been promising approaches to tackling biofilm-associated infections. Here, we have used a bacterium that produced indole terpenoid Rhodethrin (Rdn) with a combination of known antibiotic chloramphenicol (Chpl) against E. faecalis (ATCC 19433) . The fractional inhibitory concentration index (FICI) values showed between 0.25 and 0.33 synergistic activities. The exopolysaccharides (EPSs) production significant decrease with Rdn (34.6 ± 4.6%), Chpl (31.0 ± 5.2%), and combination (Rdn-Chpl) (76.0 ± 4.5%) ( p  > 0.05). However, the biofilm interruption can attenuate of total bioﬁlm was shown with Rdn (39.7 ± 5.1%), Chpl (32.6 ± 4.7%), and Rdn-Chpl (69.0 ± 5.3%), ( p  > 0.05). The microscopic observations reveal that the gradually unstructured biofilm architecture in E. faecalis. Furthermore, in silico, studies on biofilm-associated proteins (GelE, LuxS), virulence regulating (SprE), and cell division (FtsZ) have resulted in high and reasonable binding affinity, respectively. Thus, our results suggested that the synergism of Rdn-Chpl has the potential to function as a combinatorial antibiotic accelerates in treating vancomycin-resistant Enterococcus faecalis infections. Highlights: Antibacterial and antibiofilm property of Rhodethrin and synergizes with Chloramphenicol against Enterococcus faecalis. Significant reduction of EPS, Protein, and e DNA were detected in biofilm with sub MIC of Rdn and Chpl alone and combination. Molecular docking studies of protein ligands GelE, SprE, LuxS, and FtsZ gives insight of binding affinity. Synergism of Rdn-Chpl as combinatorial antibiotics for treating nosocomial pathogens.